Brolucizumab: A Newly Developed Anti-VEGF Molecule for the Treatment of Neovascular Age-Related Macular Degeneration - Tadayoni, Ramin; Sararols, Laura; Weissgerber, Georges; Verma, Rohini; Clemens, Andreas; Holz, Frank G (Ophthalmologica (Basel), 2021)
Despite the success of anti-vascular endothelial growth factors (anti-VEGFs), currently, there is a need for highly effective compounds that can alleviate the burden of managing neovascular age-related macular degeneration (nAMD). To review the milestones in the molecular and clinical development of brolucizumab, the first single-chain antibody fragment (scFv) designed specifically for intraocular use in humans. In this article, we summarize the preclinical and current clinical evidence of brolucizumab administration with an overview of the other treatment regimens and additional indications under investigation. The unique molecular design of brolucizumab led to a low molecular weight of only 26 kDa, allowing for a concentrated molar dose of 1 intravitreal injection compared with other anti-VEGF agents. Phase I and II clinical trial outcomes validated the efficacy of brolucizumab in the treatment of nAMD with signals of a more durable treatment effect. The pivotal phase III trials, HAWK and HARRIER, which included a total of 1,817 patients, established that brolucizumab can be administered every 3 months while maintaining disease control. The preclinical and clinical data on brolucizumab provide evidence of sustained disease control with longer injection intervals, thus potentially reducing the treatment burden in patients with nAMD.